Global genomics analysis of the rodent malaria parasites Plasmodium Berghei, Plasmodium Chabaudi and Plasmodium Yoelii with emphasis on the identification of novel virulence factors in Plasmodium Yoelii - Liew, Kingsley Jiin Liang (2010)
The incompletely sequenced and annotated genomes of the rodent malaria parasite (RMP) species were re-annotated via complementary genomic DNA hybridizations and bioinformatics tools. A common ’core’ set of orthologous Plasmodia genes was then elucidated. Similarly, a RMP specific ortholog gene set was also elucidated. Comparative genomics of different P. yoelii lines confirmed the presence of polymorphic genes under immune selection pressure and revealed potential variant hypothetical genes containing transmembrane domains that may be involved in novel parasite-host interactions. Next, transcriptomic differences between the virulent YM and avirulent YA lines of P. yoelii were determined and genes that are linked to virulence were identified. Two of these genes (PySERA 1 & 2) were further characterized using knockout strategies. While disruption of PySERA1 appears to reduce parasite virulence, there is no apparent effect in the case of disruption of PySERA2, thus suggesting a certain degree of redundancy of this multigene family.